Inhaled Surfactant in the treatment of accidental Talc Powder inhalation: a new case report - Lo Piparo Caterina; Vitulo Patrizio; Maggio Maria; Collura Mirella; Matina Federico; Corsello Giovanni (BMC, 2011)
Abstract The use of talcum powder is incorrectly part of the traditional care of infants. Its acute aspiration is a very dangerous condition in childhood. Although the use of baby powder has been discouraged from many authors and the reports of its accidental inhalation have been ever more rare, sometimes new cases with several fatalities have been reported. We report on a patient in which accidental inhalation of baby powder induced severe respiratory difficulties. We also point out the benefits of surfactant administration. Surfactant contributed to the rapid improvement of the medical and radiological condition, preventing severe early and late complications and avoiding invasive approaches.